Tinjauan Mendalam tentang Filsafat Hukum: Mengurai Akar Pemikiran di Balik Sistem Hukum - Nadia Mardesya; Rasji Rasji (Journal on Education, 2023)
Legal philosophy shapes, guides, and provides an ethical context for the legal system. With a focus on philosophical thinking as the basis for behavior and social interaction, the role of legal philosophy in shaping the modern legal system and its relevance in responding to social challenges and contemporary policies are highlighted. The literature review method is employed to investigate, analyze, and synthesize relevant literature on the research topic. The impact of legal philosophy on shaping social order, the fundamental concepts of law, principles of justice, and the evolution of the legal system are discussed. Contributions from figures such as Locke, Kant, and Hart delve into perspectives on values, morality, and the role of law. Legal philosophy also influences the formation of positive law and naturalism, playing a role in social contract theory, utilitarianism, and progressivism. Its influence is also evident in the concepts of human rights, justice, and governmental responsibility. Legal philosophy promotes law-conscious citizenship by encouraging critical thinking and active participation in legal and political processes.